THE ROLE OF PROJECT MANAGERS IN IMPROVING CONSTRUCTION PROJECT EFFICIENCY - Frendy Laurenza; Heri Sujatmiko; Dimas Aji Purnomo (RADJA PUBLIKA, 2025)
The construction industry faces various efficiency issues in project implementation. Construction projects often experience delays, cost overruns, and sub-optimal quality. Researchers observed that the role of project managers is crucial in creating work efficiency. Project managers are responsible for coordination, communication, decision-making, and risk management during the construction process. This study aims to analyze the contribution of project managers' roles to increasing construction project efficiency. This study uses a deductive qualitative approach that relies on literature reviews and thematic analysis from various academic sources. Researchers found that high managerial skills affect the effectiveness of resource allocation and project time. Researchers also found that open communication encourages harmonious and productive teamwork. Researchers noted that data-based decisions accelerate the problem-solving process and prevent project delays. Researchers saw that systematic risk management can reduce the impact of uncertainty and increase project stability. Researchers observed that organizational support strengthens the position of project managers in strategic decision-making. Researchers concluded that the role of project managers significantly affects all dimensions of construction project efficiency. Researchers suggest that construction companies improve project manager competencies through integrated training and supporting information systems. Researchers hope that the results of this study will contribute to efficient and sustainable project management practices. Researchers recommend a holistic approach in developing project management in the construction sector.